A construção do leitor em Tolkien: um estudo do Fórum Valinor - CHAGAS, Natallie Nazareth Alcântara (2017)
It seeks to understand the formation of the reader from the works of John Ronald Reuel Tolkien. In this direction, use as a corpus the best known novels of this english writer, namely: The Hobbit, The Lord of the Rings and The Silmarillion. In conducting the study, follows a qualitative approach, whereby Tolkien readers belonging to the forum called Valinor are taken as research subjects. As a tool for data collection adopts the questionnaire, used in gathering evidence about their relationship with the author and readers with the works analyzed. Build the biographical and theoretical overview with the aid of literature through the survey and the reading of books, articles and dissertations. Checks that the Tolkien reader has contact with the works in focus from the books, rock music, Role Playing Game (RPG) and film trilogy The Lord of the Rings. Readers will recognize in Tolkien's works a source of information, knowledge and pleasure. Finally, it considers that mediation strategies of reading are most successful when teachers and librarians know more deeply the work and its author toward the construction of the habit of reading.